Association Between Antidepressant Efficacy and Interactions of Three Core Depression-Related Brain Networks in Major Depressive Disorder - Wang, Qiang; Tian, Shui; Zhao, Peng; Cao, Qiuyun; Lu, Qing; Yao, Zhijian (Frontiers in Psychiatry, 2022)
Background: The central executive network (CEN), salience network (SN) and default mode network (DMN) are the three most studied depression-related brain networks. Many studies have shown that they are related to depression symptoms and treatment effects. However, few studies have related these three networks and their activity frequency bands to depressive symptoms and treatment efficacy. Methods: Sixty-six medication-free patients with major depressive disorder (MDD) were enrolled. Magnetoencephalography (MEG) was administered at baseline to calculate imaging indicators such as the power and functional connectivity (FC) of each brain network. The Hamilton Rating Score for Depression (HRSD-17) was assessed at baseline and weekly for 4 weeks. Pearson correlation and receiver operating characteristic curves (ROC) analyses were used to explore the relationship between brain imaging indicators and antidepressant efficacy. Results: The difference between therapeutically effective and ineffective groups was mainly manifested in the beta power of the SN. The FC of beta waves between the three networks was related to antidepressant efficacy, with ROC analysis results of AUC = 0.794, P = 0.004, sensitivity = 76.7%, and specificity = 81.8%. Limitations: The sample size was small and a healthy control group was not available. Conclusions: The interaction between the three networks is related to antidepressant efficacy and the relief of depressive symptoms.